How not to make a ranking of universities. The Peruvian case. - Velázquez Fernández, Ángel Ramón (2020)
The objective of this study was to analyze compliance with the Berlin Principles by the rankings prepared by Sunedu, as well as to evaluate their reliability, by comparing them with other rankings (THE, SIR y QS). The design has been non-experimental, descriptive, with a mixed approach. The sample consisted of twenty Peruvian universities classified in the Sunedu rankings, selected in a non-probabilistic way, based on the research objectives. As main results, it was obtained that the usefulness of the Sunedu rankings is minimal, since, by focusing only on research, the asymmetry of information on the quality of the training process does not decrease, therefore. it is not possible for young people and parents to make adequate decisions based on their results. Its sole function has been to classify universities based on a set of subjective criteria selected by a group of experts from a small number of universities. Likewise, it is appreciated that the Sunedu rankings suffer from a series of weaknesses that violate the recommendations of the Berlin Principles and reproduce the negative aspects of these classifications, which had already been warned by various specialist authors on the subject.